Associations between the Department of Veterans Affairs' Suicide Prevention Campaign and Calls to Related Crisis Lines. (November 2014) - Bossarte, Robert M.; Karras, Elizabeth; Lu, Naiji; Tu, Xin; Stephens, Brady; Draper, John; Kemp, Janet E.
Objective: The Transit Authority Suicide Prevention (TASP) campaign was launched by the Department of Veterans Affairs (VA) in a limited number of U.S. cities to promote the use of crisis lines among veterans of military service. Methods: We obtained the daily number of calls to the VCL and National Suicide Prevention Lifeline (NSPL) for six implementation cities (where the campaign was active) and four control cities (where there was no TASP campaign messaging) for a 14-month period. To identify changes in call volume associated with campaign implementation, VCL and NSPL daily call counts for three time periods of equal length (pre-campaign, during campaign, and post-campaign) were modeled using a Poisson log-linear regression with inference based on the generalized estimating equations. Results: Statistically significant increases in calls to both the VCL and the NSPL were reported during the TASP campaign in implementation cities, but were not reported in control cities during or following the campaign. Secondary outcome measures were also reported for the VCL and included the percentage of callers who are veterans, and calls resulting in a rescue during the study period. Conclusions: Results from this study reveal some promise for suicide prevention messaging to promote the use of telephone crisis services and contribute to an emerging area of research examining the effects of campaigns on help seeking.